2017
DOI: 10.4067/s0718-95162017005000036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pseudomonas aeruginosa MAJ PIA03 affecting the growth and phytonutrient production of castor, a primary host-plant of Samia ricini

Abstract: Castor (Ricinus communis L.) is a primary food plant of eri silkworm, Samia ricini Donovan endemic to Northeast India. Plant growth promoting rhizobacteria (PGPR) plays crucial role in growth and productivity of agricultural crops. Eighty-five Pseudomonas strains were isolated from thirty rhizosphere soil samples of castor and their in vitro potentiality was screened for growth promoting ability and antifungal potentialities. Most of the selected Pseudomonas sp. produced indole acetic acid, gibberellic acid, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The higher severity of disease in the treatment given P. aeruginosa RE081 compared to the control is thought to be due to increased nutrients, especially P and N in the growing media for E. Pellita seedlings. Research conducted in vitro by Marfungah et al (2023) reported that the characteristics of P. aeruginosa RE081 as a biocontrol agent could produce siderophores, HCN, Protease, IAA, and solvent P. This was confirmed by other research reported by Sandilya et al al. (2017), who stated that the Pseudomonas aeruginosa strain MAJPIA03 bacteria is capable of producing NH3, HCN, siderophores, ACC deaminase, IAA, and gibberellins.…”
Section: Test the Effect Of P Aeruginosamentioning
confidence: 62%
“…The higher severity of disease in the treatment given P. aeruginosa RE081 compared to the control is thought to be due to increased nutrients, especially P and N in the growing media for E. Pellita seedlings. Research conducted in vitro by Marfungah et al (2023) reported that the characteristics of P. aeruginosa RE081 as a biocontrol agent could produce siderophores, HCN, Protease, IAA, and solvent P. This was confirmed by other research reported by Sandilya et al al. (2017), who stated that the Pseudomonas aeruginosa strain MAJPIA03 bacteria is capable of producing NH3, HCN, siderophores, ACC deaminase, IAA, and gibberellins.…”
Section: Test the Effect Of P Aeruginosamentioning
confidence: 62%
“…The highest IAA producing strain was B49 (35.15±0.76 μg/ml) followed by B46 (28.59±0.05 μg/ml) and B4 (26.98±0.42 μg/ml). Sandilya et al (37) reported that eight Pseudomonas spp. isolates derived from castor rhizosphere showed IAA production in vitro ranged from 5.19 μg/ml to 27.84 μg/ml.…”
Section: Indole-3-acetic Acid (Iaa) Productionmentioning
confidence: 99%
“…Biosynthesis of IAA by Pseudomonas aeruginosa has been widely reported [59][60][61][62][63][64][65][66][67][68]; however, only a few studies have reported the production of GA3 by Pseudomonas aeruginosa [67][68][69]. Although cytokinin compounds have also been reported to be produced by Pseudomonas aeruginosa, there are quite a few reports on the biosynthesis of zeatin, and kinetin by this bacterial genus [68,[70][71][72].…”
Section: Assessment Of the Potential Biocontrol Of Robusta Coffee Nematodes And Plant-promoting Effect Of Pseudomonas Aeruginosa Tun03 Unmentioning
confidence: 99%